Exploring a New Measure for Reactive Guilt Appeals - Lwin, Michael; Phau, Ian (Australian and New Zealand Marketing Academy, 2012)
Literature identifies three classifications of guilt namely, reactive, anticipatory, and existential guilt. Scholars have shown that specific types of guilt appeals can be effective in advertising (e.g. Hibbert et al. 2007). However researchers have relied on the use of unified guilt scale as a measure of specific types of guilt. Thus the paper highlights the inherent need for a specific scale. Using two studies, the research attempts to reach the gap in literature by developing a measure of consumer’s reactive guilt to advertising stimulus. The research is one of the first to explore a scale for reactive guilt in an advertising context. Considering the importance of the guilt appeals in advertising, the scale will be an effective tool for practitioners and scholars.